Aryl hydrocarbon receptor-mediated and estrogenic activities of oxygenated polycyclic aromatic hydrocarbons and azaarenes originally identified in extracts of river sediments - Machala, M; Ciganek, M; Bláha, L; Minksová, K; Vondráck, J (Environmental toxicology and chemistry, 2001)
Reproductive dysfunction in wildlife populations can be a result of environmental contaminants binding to aryl hydrocarbon receptor (AhR) or estrogenic receptors. Signaling by both types of receptors can be affected by polycyclic aromatic hydrocarbons (PAHs), which are potential endocrine disruptors. However, our knowledge regarding the effects of oxygenated (oxy)-PAHs and azaarenes on AhR-mediated and estrogenic activities is incomplete. In the present study, we have identified 9-fluorenone, anthrone, anthraquinone, benzanthrone, benz[a]anthracene-7,12-dione, benz[c]acridine, and dibenz[a,h]acridine as prevalent oxy-PAHs and azaarenes found in river sediments. Their concentrations in sediment samples ranged from 2.1 to 165.2 ng g(-1) for oxy-PAHs and up to 27.3 ng g(-1) for azaarenes. Their relative AhR-inducing and estrogenic potencies were quantified in vitro using two cell lines that were stably transfected with a luciferase reporter gene system and expressed as induction equivalency factors (IEFs). The only oxy-PAHs with detectable levels of in vitro AhR-mediated activity were benzanthrone and benz[a]anthracene-7,12-dione. However, their IEFs were approximately three to four orders of magnitude lower than those of benzo[a]pyrene. On the other hand, azaarenes showed a strong AhR-mediated activity, with dibenzo[a,h]acridine being a far more potent inducer of activity than benzo[a]pyrene. Benzanthrone, benz[a]anthracene-7,12-dione, anthraquinone, and benz[a]acridine were weak inducers of in vitro estrogenic activity, with IEFs similar to that of benzo[a]pyrene. Based on concentrations and relative potencies, our results suggest that dibenzo[a,h]acridine can significantly contribute to the overall AhR-mediated activity in river sediments, whereas the remaining compounds do not. No studied compound was found to contribute significantly to estrogen receptor-mediated activity in vitro.
Keywords: Luciferases; receptory pro estrogeny; Gene Expression Regulation; Receptors, Estrogen; receptory aromatických uhlovodíků; Oxygen; geologické sedimenty; luciferasy; reportérové geny; Carcinoma, Hepatocellular; polycyklické aromatické uhlovodíky; krysa rodu Rattus; Geologic Sediments; Animals; kyslík; zvířata; regulace genové exprese; Rats; hepatocelulární karcinom; nádorové buňky kultivované; Tumor Cells, Cultured; Liver Neoplasms; Genes, Reporter; nádory jater; Receptors, Aryl Hydrocarbon; Polycyclic Aromatic Hydrocarbons